An LC-MS/MS Method Development and Validation for the Quantification of Infigratinib in K2EDTA Human Plasma (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
A validated liquid chromatography with tandem mass spectrometry (LC-MS-MS) technology was developed for the quantification of infigratinib, using a simple and specific approach. This method utilizes a liquid-liquid extraction (LLE) strategy to achieve high sensitivity. The analytical approach that was developed underwent validation in terms of many characteristics including specificity, sensitivity, carry-over, recovery, precision, matrix effect, accuracy, and stability. The elution of the drug and IS occurred in a time frame of 6.5 minutes using a PhenomenexSB-C18 column (250 × 4.6 mm x 5 μm). The mobile phase consisted of a mixture of acetonitrile and 0.1% v/v formic acid in water, with a ratio of 80:20. The infusion flow rate was set at 0.9 mL/min. The retention times (RT) of infigratinib and IS were determined to be 5.12 and 3.31 minutes, respectively. The elution time required for complete separation of infigratinib was 6.5 minutes. The equation of the linear regression line was determined to be y = 0.994x + 2.662, and the coefficient of determination (r2) was calculated to be 0.999. The coefficient of variation (%CV) obtained for the calibration graph of infigratinib was determined to be less than or equal to 3.73. The matrix effect was assessed by calculating the coefficient of variation (%CV) for the High and low quality control (QC) samples, yielding values of 1.64 and 0.70% respectively.